Cloning, expression analysis, and functional identification of ELF5 gene in Wanlin white goat (Capra hircus)(皖临白山羊ELF5基因克隆、表达分析及功能鉴定) - YU Yajie(余雅杰); GUO Yuzhu(郭玉柱); MA Cunxia(马存霞); TU Tongtong(土彤彤); LIU Hongyu(刘洪瑜); ZHANG Yunhai(张运海); SONG Ning(宋宁) (Zhejiang daxue xue bao. Journal of Zhejiang University. Agriculture and life sciences. Nong ye yu sheng ming ke xue ban, 2025)
In order to clarify the gene sequence, structure and expression of E74 like ETS transcription factor 5 (ELF5) in goat mammary gland and the effect of ELF5 gene on β-casein (CSN2) expression, this study took Wanlin white goat mammary epithelial cells as the experimental model and cloned the coding region sequence of ELF5 gene by polymerase chain reaction. The expression patterns of ELF5 gene in goat mammary gland at early, peak, middle, late and dry lactations were detected, and bioinformatics analysis was conducted using online software. After overexpression and inhibition of ELF5 gene, casein-related genes were detected. The results showed that the complete coding region of goat ELF5 gene is 768 bp long and encodes 255 amino acids. The molecular weight of the protein is 30 089.83 Da, and the theoretical isoelectric point is 5.61. There are 31 phosphorylation sites, without signal peptide and transmembrane helix structure. ELF5 is an unstable protein carrying negative charge. ELF5 interacts with prolactin receptor (PRLR), β-casein, estrogen related receptor beta (ESRRB), forkhead box A1 (FOXA1), and so on. Goat ELF5 gene is closely associated to sheep and cattle. The expression levels of ELF5 and CSN2 genes were greater in early, peak and middle lactations of goats. In goat mammary epithelial cell models, overexpression of ELF5 increased the expression level of β-casein, whereas interference with ELF5 had the opposite effect, suggesting that ELF5 gene could promote β-casein synthesis in goat mammary epithelial cells. This study provides a theoretical basis for the study on the regulatory mechanism of β-casein synthesis by ELF5 gene during goat lactation.(为阐明E74样ETS转录因子5（E74 like ETS transcription factor 5, ELF5）在山羊乳腺中的基因序列、结构、表达情况以及ELF5基因对β-酪蛋白（beta-casein, CSN2）表达的影响，本研究以皖临白山羊乳腺上皮细胞为试验模型，通过聚合酶链反应克隆ELF5基因编码区序列，检测ELF5基因在山羊乳腺泌乳初期、盛期、中期、后期以及干奶期的表达模式，同时利用在线软件进行生物信息学分析，对过表达与抑制ELF5基因后酪蛋白相关基因表达进行检测。结果显示，本研究克隆得到山羊ELF5基因完整编码区，长768 bp，编码255个氨基酸；ELF5蛋白分子量为30 089.83 Da，理论等电点为5.61，存在31个磷酸化位点，无信号肽和跨膜螺旋结构，为携带负电荷的不稳定蛋白。ELF5与催乳素受体（prolactin receptor, PRLR）、雌激素相关受体β（estrogen related receptor beta, ESRRB）、β-酪蛋白、叉头盒蛋白A1（forkhead box A1, FOXA1）等蛋白质存在互作；山羊ELF5基因与绵羊、牛的亲缘关系最近；ELF5和CSN2基因在山羊泌乳初期、盛期和中期的表达水平较高。在山羊乳腺上皮细胞模型中，过表达ELF5可使β-酪蛋白的表达水平升高，干扰ELF5的结果则与之相反，表明ELF5基因能促进山羊乳腺细胞中β-酪蛋白的合成。本研究为开展ELF5基因在山羊泌乳过程中β-酪蛋白合成的调控机制研究提供了前期理论依据。)